Elegant Hermite–Gaussian and Laguerre–Gaussian beams at a dielectric interface - Nasalski, Wojciech (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Basic features of narrow optical beam interactions with a dielectric interface are analysed. It is shown that two types of paraxial beams – elegant Hermite–Gaussians of linear polarization and elegant Laguerre–Gaussians of circular polarization – can be treated as vector normal modes of the interface. Excitation of higher-order modes by cross-polarization coupling is described and changes of mode indices induced by transmission and reflection matrices are evaluated. Optical vortex excitation and splitting are theoretically predicted and confirmed by numerical simulations.
Optica Applicata, Vol. 40, 2010, nr 3, s. 615-622
Keywords: optyka; Hermite–Gaussian and Laguerre–Gaussian beams; dielectric interfaces; total internal reflection; optical vortices and cross-polarization coupling